Cytokine genetic profile in Whipple’s disease - Biagi, Federico; Mytilineos, Joannis (European journal of clinical microbiology & infectious diseases, 2012)
Whipple’s disease (WD) is a very rare chronic systemic condition characterised by a Th2/T regulatory (Treg) dysregulated immune response versus Tropheryma whipplei, a bacterium widely diffuse in the environment. To investigate whether this Th2/Treg polarised response has a genetic background, we investigated the Th1, Th2, Th17 and Treg cytokine genetic profile of 133 patients with WD. Thanks to the European Consortium on WD (QLG1-CT-2002-01049), the polymorphism of 13 cytokine genes was analysed in 111 German and 22 Italian patients using the polymerase chain reaction with sequence-specific primers (PCR-SSP) technique. The frequencies of the genotypes, haplotypes and functional phenotypes were compared with those obtained in 201 German and 140 Italian controls. Clinical heterogeneity was also considered. Functionally, WD patients may be considered as low producers of TGF-β1, having an increased frequency of the genotype TGF-β1+869C/C,+915C/C [12.3 % vs. 3.81 %, odds ratio (OR) = 4.131, p = 0.0002] and high secretors of IL-4, carrying the genotype IL-4-590T/T (5.34 % vs. 1.17 %, OR = 5.09, p = 0.0096). No significant association was found between cytokine polymorphism and clinical variability. Analogously to the recent cellular findings of a Th2/Treg polarised response, we showed that the cytokine genetic profile of WD patients is skewed toward a Th2 and Treg response. This was similar in both German and Italian populations. However, the significant deviations versus the controls are poorer than that expected on the basis of these recent cellular findings.
First online: 31 July 2012
Gesehen am 20.06.2018